2005
DOI: 10.1074/jbc.m413730200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Gastrointestinal Glutathione Peroxidase Is Inversely Correlated to the Presence of Hepatitis C Virus Subgenomic RNA in Human Liver Cells

Abstract: There is great medical need to develop novel therapies for treatment of human hepatitis C virus (HCV). By gene expression analysis of three HCV-subgenomic RNA replicon cell lines, we identified cellular proteins whose expression is affected by the presence of HCV and therefore may serve as drug targets. Data from cDNA array filter hybridization, as well as from Northern and Western blotting, revealed that the gastrointestinal-glutathione peroxidase (GI-GPx) was drastically down-regulated (up to 20-fold) in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 53 publications
2
40
1
Order By: Relevance
“…We downregulated the expression of GPX2 in A549 cells by using siRNA targeting GPX2 mRNA ( Figure 7A) (22). To Western blot analysis of A549 cells transfected with Nrf2, keap1, or SS siRNA.…”
Section: Silencing Of Gpx2 By Sirna Sensitizes the Lung Epithelial Cementioning
confidence: 99%
“…We downregulated the expression of GPX2 in A549 cells by using siRNA targeting GPX2 mRNA ( Figure 7A) (22). To Western blot analysis of A549 cells transfected with Nrf2, keap1, or SS siRNA.…”
Section: Silencing Of Gpx2 By Sirna Sensitizes the Lung Epithelial Cementioning
confidence: 99%
“…Glutathione peroxidase and catalase are key enzymes regulating the levels of ROS and protecting cells from ATO-induced damage (26). However, the gastrointestinal glutathione peroxidase was drastically downregulated in cells harboring HCV replicons, which are rendered more susceptible to oxidative stress (39). The glutathione redox system has been implicated in the cellular defense system (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not surprising given the lack of known direct anti-viral effects of antioxidants. A study reported that induction of gastrointestinal glutathione oxidase (which counteracts oxidative stress) by all trans retinoic acids, down-regulates HCV replicon in cell lines [6] . Adverse events that are attributable to therapy such as exacerbation of hypertension, pedal edema, and hypokalemia, are mostly related to pseudoaldosteronism associated with the 11-hydroxy-steroid dehydrogenase inhibitory activity of glycyrrhiza and L-glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…These processes may contribute to fibrosis and carcinogenesis in chronic HCV [5] . Analysis of HCV-sub genomic RNA replicon cell lines has shown a drastic reduction in cellular glutathione peroxidase, increasing cellular susceptibility to oxidative stress [6] . Based on these data, a rationale for antioxidant treatment of chronic hepatitis C was suggested.…”
Section: Introductionmentioning
confidence: 99%